Development of a Training Program to Enhance Entrepreneurship Competencies of Higher Education Students - Preedawiphat, Tatsawan; Ponathong, Chakrit; Yongsorn, Chatupol (Ratchaphruek Journal, 2022)
This research studied the essential competencies based on current and future entrepreneurship competencies. The purposes to develop such a training program were to enhance the entrepreneurship competencies of higher education students. The sample group were; 15 of students, professors, and university administrators in 5 universities, 400 of entrepreneurs/employers who participated with 5 university students, 7 experts who experienced in entrepreneurship education, and 30 higher education students. The research instruments consisted of a questionnaire, a training program, and an evaluation form for the effectiveness of the training program. The statistical data were analyzed by mean, standard deviation, Priority Needs Index (PNIModified) to synthesize 12 entrepreneurship competencies, and t-test for dependent sample. The results showed that 1) The six highest competencies appropriate to empirical data were critical thinking, embracing ambiguity, collaboration, communication, empathy, and creativity. 2) Development of a training program by using the standard component weights that statistically significantly higher than PNIModified 3.6. 3) The learning outcomes of the samples after the training were statistically significant (a = .01).